Segregation of study items in memory determines the magnitude and direction of directed forgetting. (5th March 2012) - Icht, Michal; Chajut, Eran; Algom, Daniel
<x xml:space="preserve">Abstract</x> When words at study are divided into to‐be‐remembered and to‐be‐forgotten ones, people recall more of the former than of the latter in a surprise memory test for all words. In this study, we also tapped memory for word identity at study (forget or remember) by asking participants to reproduce in memory selected portions of the original words. We found word identity to be parasitic on word reproduction. As a result, there is a noted tendency to recall forget‐words from study as remember‐words in the memory test more than vice versa.